SYNTHESIS AND PHOTOCATALYTIC ACTIVITY OF TIO 2 /AG - S. A. P. V. T. de Carvalho, E. A. Pereira, M. A. Montanhera & Y. J. Dias, F. R. de Paula* (International Journal of Research Science and Management, 2018)
Over the last decade, titanium dioxide (TiO2), in particular, anatase phase became the most studied semiconductor photocatalyst due to its high photocatalytic efficiency under UV irradiation, low cost, high stability, and low toxicity. These characteristics allow the degradation of toxic and biological waste present in air and water, efforts have been devoted to modify and enhance them. In this work, TiO2 samples were synthesized with different silver carbonate (Ag2CO3) concentrations. Under UV light, the results showed an enhancement in photocatalytic performance in degradation of Rhodamine-B dye compared to pure TiO2. An increase of 25% on Rhodamine-B by TiO2/Ag degradation was noticed.